New resources for genetic studies in maize (Zea mays L.): a genome‐wide Maize6H‐60K single nucleotide polymorphism array and its application. (14th December 2020) - Tian, Hongli; Yang, Yang; Yi, Hongmei; Xu, Liwen; He, Hang; Fan, Yaming; Wang, Lu; Ge, Jianrong; Liu, Yawei; Wang, Fengge; Zhao, Jiuran
SUMMARY: Despite the availability of numerous molecular markers in maize, effective evaluation of all types of germplasm resources, accurate identification of varieties and analysis of a large number of materials in a timely, low‐cost manner is challenging. Here, we present Maize6H‐60K, a genome‐wide single nucleotide polymorphism (SNP) array to facilitate maize genotyping. We first identified 160 million variants by sequencing data of 388 representative inbreds and then tiled 200 000 high‐quality variants on a screening array. These variants were further narrowed down to 61 282 using stringent filtering criteria. Among the 60 000 markers, 21 460 SNPs (35%) were within genic regions and 12 835 (21%) were located in coding regions. To assess their effectiveness, 329 inbreds, 221 hybrids, 34 parent–offspring sets and six breeding samples were genotyped. Overall, 48 972 SNPs (80%) were categorized into the highest quality class, that of 'poly high resolution'. A total of 54 658 (89.29%) and 53 091 (86.73%) SNPs had minor allele frequency values ≥ 0.20 in inbreds and hybrids respectively. A linkage disequilibrium (LD) analysis revealed that LD decline was in equilibrium when r 2 was between 0.10 and 0.15, which corresponds to a physical distance of 400–600 kb. UPGMA clustering analysis divided the 329 inbred lines into nine groups that were consistent with known pedigrees. A background analysis of breeding materials indicated that the 60 000 markers were suitable for evaluation of breeding populations constructed by materials between or within heterotic groups. The developed Maize6H‐60K array should be an important tool in maize genetic studies, variety identification and molecular breeding. Significance Statement: The development of single nucleotide polymorphism (SNP) arrays in maize, one of the most important crops, has lagged behind that of other crops. To facilitate maize genotyping, we have accordingly developed the Maize6H‐60K SNP array based on the whole genome sequence data of 388 globally collected inbred lines. Our findings suggest that the Maize6H‐60K array, with its high density, high quality and high efficiency, should be an important tool in maize molecular genetics studies.